An Analysis of Service Quality and Consumer Satisfaction from the Perspective of Islamic Business Ethics - Zulfi; Musthofa , M Arif; Nurjali; Fatimah, Siti; Dewi, Hasna (CV. Civiliza Publishing, 2025)
Grocery businesses represent a popular form of entrepreneurship within communities due to their easy accessibility, stable market demand, and relatively affordable capital requirements. Amidst the intense competition in the retail sector, service quality and the application of business ethics are critical to success. This study aims to evaluate the service quality of April Grocery Store in Kota Baru Village through the lens of Islamic business ethics, encompassing principles such as honesty (ṣidq), trustworthiness (amānah), justice (ʿadl), and excellence (iḥsān). Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation involving the store owner, employees, and customers. The findings indicate that although ethical values have been incorporated into sales interactions and service practices, challenges remain in operational aspects, including the absence of standardized service procedures, infrastructural limitations, and suboptimal adaptation to the needs of modern consumers. The study concludes that integrating Islamic ethical values with professional service management can enhance customer satisfaction and support the sustainability of small-scale enterprises in a competitive market environment.